TRAINING ON ECOPRINTING POUNDING TECHNIQUE BY UTILIZING ENVIRONMENTAL POTENTIAL IN ENHANCING CREATIVITY AND ENTREPRENEURSHIP SKILLS OF STUDENTS - Arini Rahma Dhani; Yusnaeni Yusnaeni; Andam S. Ardan; Angela G. Lika; Mbing Maria Imakulata; Nikmah Nikmah; Maryanto C. Honin (Universitas Muhammadiyah Lamongan, 2024)
One of the soft skills that need to be honed for students is creativity. Creativity is the courage to try new ideas and look for alternative answers to the problems faced. The existence of creative souls can later become an asset in building an entrepreneurial spirit. Ecoprint is one of the media to hone students' creativity while exploring the potential of the surrounding natural environment. Ecoprint is the transfer of natural original colors on fabrics that have high absorption. There are several techniques used to produce ecoprint motifs including pounding, boiling and steam techniques. The pounding technique means beating the leaves on a piece of white cloth. This beating is used to bring out the natural colors in the leaves/flowers. The purpose of this training is to hone students' creativity and develop the spirit of entrepreneurship through ecoprint training that utilizes environmental potential. The method used was in 4 stages, namely, preparation, socialization, training and evaluation. The participants of this ecoprint training were very enthusiastic. This is shown by the results of a survey via google form to students regarding the suitability of the training objectives, the attractiveness of the material, the way of delivery of the speakers, the ease of practicing ecoprinting. The survey results showed 90% of students were satisfied with the activity.